Compassionate Imagining - Jack, Chelsea A. (The Hastings Center report, 2015)
I will always remember my first months at The Hastings Center as set against a backdrop of calls for social justice and the protection of vulnerable populations. Following weeks of civil unrest sparked by police brutality in Ferguson, Missouri, the fatal strangulation of Eric Garner, a black man, by a white New York police officer gave rise to “die-ins” across the country. I blogged for Bioethics Forum on the Ebola outbreaks in Guinea, Liberia, and Sierra Leone, with a focus on retrofitting governance systems that ignored a dangerous lack of health infrastructure and created populations vulnerable to public health emergencies. Back home in Virginia, I celebrated with family and friends the legalization of same-sex marriage after the Supreme Court let stand rulings in favor of it in five states. Voices of protest have focused our attention on the injustices faced by populations made vulnerable, particularly people of color, the poor, victims of public health crises, and lesbian, gay, bisexual, transgender, and queer communities.